Perception and Prejudice: Attention and Moral Progress in Iris Murdoch's Philosophy and C. S. Lewis's A Grief Observed - Forsberg, Anders Niklas (Hebrew University of Jerusalem, 2020)
It might seem intuitive to say that attention is a matter of looking really closely at something, zeroing in on a particular object. In contrast to such an understanding of attention, it is here argued that attentive understanding of particular persons, things or events can only be apprehended by means of attending to the world in which they belong. Iris Murdoch's example of M and D is often described as a clear illustration of what "attention" is. I argue that the example is rather unhelpful, precisely because we get no description of the work of attention. There is, therefore, a hole in the argument. The strategy of this paper is to fill that hole by means of a reading of C. S. Lewis's A Grief Observed. Here a clear view of another person is attained by attention to the world together with unearthing one's own prejudices—a view shared by Murdoch but missing in the reception of her thought.
Keywords: love; láska